Stability of Skin Microbiome at Sacral Regions of Healthy Young Adults, Ambulatory Older Adults, and Bedridden Older Patients After 2 Years. Issue 1 (January 2021) - Ogai, Kazuhiro; Ogura, Kohei; Ohgi, Nozomi; Park, Seohui; Aoki, Miku; Urai, Tamae; Nagase, Satoshi; Okamoto, Shigefumi; Sugama, Junko
Objective: The sacral skin of bedridden older patients often develops a dysbiotic condition. To clarify whether the condition changes or is sustained over time, we analyzed the skin microbiome and the skin physiological functions of the sacral skin in patients who completed our 2017 study. Methods: In 2019, we collected the microbiome on the sacral region and measured sacral skin hydration, pH, and transepidermal water loss from 7 healthy young adults, 10 ambulatory older adults, and 8 bedridden older patients, all of whom had been recruited for the 2017 study. For microbiome analysis, 16S ribosomal RNA-based metagenomic analysis was used. Results: No significant differences in the microbial compositions or any alpha diversity metrics were found in the bedridden older patients between the 2017 and 2019 studies; the higher gut-related bacteria were still observed on the sacral skin of the bedridden older patients even after 2 years. Only skin pH showed a significant decrease, approaching normal skin condition, in the bedridden older patients over 2 years. Conclusion: This study indicated that gut-related bacteria stably resided in the sacral skin in bedridden patients, even if the patient had tried to restore skin physiological functions using daily skin care. We propose the importance of skin care that focuses more on bacterial decontamination for the sacral region of bedridden older patients, in order to decrease the chances of skin/wound infection and inflammation.